Character Problems as Collective Behavior. Issue 4 (2nd October 2020) - McLuhan, Arthur
Abstract : This article presents a theory of character problems as collective behavior grounded in the empirical case of ministry formation in two Protestant Christian seminaries. An interactionist approach to character begins with some standard theoretical openings that dislodge the evaluative core of character from the putative dispositions that inhere in persons and focus analytical attention on the attribution of character in situations. One of the challenges of pursuing this theoretical strategy is the tendency in interactionism to overemphasize situations as self‐contained sites of continually emergent meaning and action, which would neglect important aspects of character that extend beyond the immediate situation. Recent directions in interactionist theorizing that tie the situations of interaction to small group cultures and temporal coordinations aim to redress this moment‐by‐moment bias, and the inter‐situational dimensions of character attributions offer the empirical purchase to apply, assess, and extend those theoretical projects.